Conceptual Model of Early Childhood Islamic Learning in Islamic Kindergarten - Ratnasih, Teti; Garnasih, Titi Ratna (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the learning model of Islamic Religious Education in early childhood of Raudhatul Athfal (RA)/ Islamic Kindergarten in Indonesia, regarding planning, objectives, material, methods, and evaluation of learning. The study used a descriptive qualitative approach. Data collection was carried out using observation, interviews, and documentation studies. The analytical methodology uses the Research and Development (R&D) approach to develop a model for creative and innovative learning in Islamic Kindergarten. Religious Learning in Early Childhood is oriented to encourage children to know and read the Qur’an, to know the religion they hold, and to know and do worship, and to have good behavior by behaving honestly, helping, polite, maintaining personal hygiene and the environment. The Islamic education learning model offered at early childhood Islamic education is the TAM Model (T is “Terampil”/ Skilled, AM is “Akhlaq Mulia”/ Noble Character), so that children have the basic competence to know and read the Qur’an and are accustomed to noble character.